2016
DOI: 10.1038/cddis.2016.3
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of NRF2 determines the self-renewal and osteogenic differentiation potential of human MSCs via the P53–SIRT1 axis

Abstract: NRF2 (nuclear factor erythroid-derived 2-like 2) plays an important role in defense against oxidative stress at the cellular level. Recently, the roles of NRF2 in embryonic and adult stem cells have been reported, but its role in maintaining self-renewal and differentiation potential remains unknown. We studied the mechanisms of NRF2 action in mesenchymal stem cells (MSCs) derived from human bone marrow. We found that the cellular localization of NRF2 changed during prolonged cell passage and osteogenic differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 60 publications
1
66
0
Order By: Relevance
“…Nrf2 (nuclear factor erythroid-derived 2-like 2) importantly defends against oxidative stress at the cellular level 19 . Expression of Sod-2, Sod-3, HO-1, and Prdx1 are regulated by Nrf2 20, 21 .…”
Section: Resultsmentioning
confidence: 99%
“…Nrf2 (nuclear factor erythroid-derived 2-like 2) importantly defends against oxidative stress at the cellular level 19 . Expression of Sod-2, Sod-3, HO-1, and Prdx1 are regulated by Nrf2 20, 21 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown bidirectional crosstalk between SIRT1 and nuclear factor erythroid 2-related factor 2 (Nrf2) in human renal proximal tubular and glomerular mesangial cells [57,58]. The upregulation of SIRT1 activates Nrf2 through the inhibition of p53 or activation of AMPK [59][60][61]. In addition, it is known that in ischemic injury Nrf2 suppresses NLRP3 inflammasome activation through regulating the thioredoxin-interacting protein (TXNIP) complex [62].…”
Section: Discussionmentioning
confidence: 99%
“…No: TRCN0000007555) was cloned into Plko.1 Tet-ON plasmid (Addgene clone ID 21915). This shRNA showed significantly better knock down of Nrf2 as reported previously in recent studies [28,29]. For generating Nrf2 overexpression plasmids, a lentiviral vector containing full-length Nrf2 cDNA, PLX304-Nrf2 (clone ID HsCD00445044), was purchased from DNASU plasmid repository (Biodesign Institute, Arizona State University, Arizona, USA).…”
Section: Methodsmentioning
confidence: 77%